Validation of Susceptibility Loci for Vitiligo Identified by GWAS in the Chinese Han Population - Cheng, Lu; Liang, Bo; Tang, Xian-Fa; Cai, Xin-Ying; Cheng, Hui; Zheng, Xiao-Dong; Zheng, Jie; Wang, Meng-Wei; Zhu, Jun; Zhou, Fu-Sheng; Li, Pan; Xiao, Feng-Li (Frontiers in Genetics, 2020)
Genome-wide association studies (GWASs) in Caucasian populations have identified 49 susceptible genes/loci associated with vitiligo. To date, some of these reported susceptibility loci have not yet been validated in the Chinese Han population. This study aims to examine whether the 16 reported susceptible loci in Caucasian populations are associated with vitiligo in the Chinese Han population. The 16 variants were imputed using our GWAS dataset by IMPUTE v2.2.2. The 16 top SNPs with suggestive signals together with the reported SNPs were genotyped in a total of 2581 cases and 2579 controls by the Sequenom platform. PLINK 2.0 software was used to perform association analyses. DbSNP, HaploReg and eQTL were adopted to annotate the biological function. Finally, four SNPs from three loci were significantly associated with vitiligo, including of rs3747517 (P = 1.29 × 10-3, OR = 0.87) at 2q24.2, rs4822024 (P = 6.37 × 10-10, OR = 0.67) at 22q13.2, rs4807000 (P = 7.78 × 10-24, OR = 0.66) and rs6510827 (P = 3.65 × 10-5, OR: 1.19) at 19p13.3. In the stratification analyses of clinical phenotypes, 22q13.2 (rs4822024) was significantly associated with segmental vitiligo patients (P = 1.76 × 10-5). In addition, 19p13.3 (rs4807000, rs6510827) and 22q13.2 (rs4822024) had significant association with non-segmental vitiligo patients (P = 2.49 × 10-16; P = 1.66 × 10-4; P = 4.87 × 10-8, respectively). Accoding to dbSNP database, rs3747517 is a missense variant of IFIH1, rs4807000 and rs6510827 are located in TICAM1, and rs4822024 is located 6kb upstream of the TEF. Further bioinformatics analysis found that rs4807000, rs6510827 and rs4822024 are involved in regulating gene expression. Our study independently replicated and suggested the strong association of 2q24.2 (IFIH1), 19p13.3 (TICAM1) and 22q13.2 (TEF) with the risk of vitiligo in Chinese Han population, and advanced the understanding of the genetic contribution to vitiligo.